The Effectiveness of Wizer.me in Developing Electronic Learning Materials: A Study with English Teacher - Nildasari Nildasari; Rafi'ah Nur (Universitas Muhammadiyah Barru, 2024)
The primary objective of this research is to investigate out teachers' responses to the ease of use and flexibility of Wizer.me in compiling LKPD. Then analyze the perceptions of students' learning outcomes in using Interactive Student Worksheets (LKPD) with the wizer.me application on English learning materials. In this research, a qualitative approach was employed, utilizing a case study method. The research was conducted at SMP Negeri 30 Makassar, involving one teacher and five students 8th grade as informants. Data were collected through interviews recorded using Voice Note on WhatsApp, a voice recorder, and picture documentation. The researchers gave six questions for both students and teachers to gather in-depth insights. The results of this study show that Wizer.me is a highly beneficial tool for both teachers and students in the context of English language education. The research findings highlight several key advantages: Easy to use, versatility, Resources accessibility, multimedia integration, and efficiency. Therefore Wizer.me proves to be an effective tool to make interactive worcksheet (LKPD) in English language education, offering ease of use, flexibility, and enhanced learning experiences. The study suggests that Wizer.me's benefits extend beyond English, making it suitable for subjects like Mathematics, Science, and Social Sciences. Future researchers should consider exploring its application in these areas to further validate its effectiveness and versatility in education.